Agricultural sustainability and environmental change at ancient Gordion - Marston, John M. (Philadelphia)
xii, 203 sayfa, [8] sayfa resim, harita
Keywords: “This book publishes the results of 220 botanical samples from the 1993-2002 Gordion excavations directed by Mary Voigt. Together with Naomi Miller's 2010 volume (Gordion Special Studies 5), this book completes the publication of botanical samples from Voigt's excavations. The book aims to reconstruct agricultural decision making using archaeological and paleoenvironmental data from Gordion to describe environmental and agricultural changes at the site. I argue that different political and economic systems implemented over time at Gordion resulted in patterns of agricultural decision making that were well adapted to the social setting of farmers in each period, but that these practices had divergent environmental impacts, with some regimes sponsoring sustainable agricultural practices and others leading to significant environmental change. The implications of this book are twofold: Gordion will now be one of the best published agricultural datasets from the entire Near East, and serve as a valuable comparable dataset for regional synthesis of agricultural and environmental change. The methods developed to reconstruct agricultural change at Gordion function as tools to engage questions about the relationship between social and environmental change at sites worldwide. Other books address similar themes but no work on the Near East address these themes in diachronic perspective as done at Gordion“ --